Supramolecular Host–Guest Hydrogels for Corneal Regeneration - Amy C. Madl; David Myung (Gels, 2021)
Over 6.2 million people worldwide suffer from moderate to severe vision loss due to corneal disease. While transplantation with allogenic donor tissue is sight-restoring for many patients with corneal blindness, this treatment modality is limited by long waiting lists and high rejection rates, particularly in patients with severe tissue damage and ocular surface pathologies. Hydrogel biomaterials represent a promising alternative to donor tissue for scalable, nonimmunogenic corneal reconstruction. However, implanted hydrogel materials require invasive surgeries and do not precisely conform to tissue defects, increasing the risk of patient discomfort, infection, and visual distortions. Moreover, most hydrogel crosslinking chemistries for the in situ formation of hydrogels exhibit off-target effects such as cross-reactivity with biological structures and/or result in extractable solutes that can have an impact on wound-healing and inflammation. To address the need for cytocompatible, minimally invasive, injectable tissue substitutes, host–guest interactions have emerged as an important crosslinking strategy. This review provides an overview of host–guest hydrogels as injectable therapeutics and highlights the potential application of host–guest interactions in the design of corneal stromal tissue substitutes.